Sequential hybrid ablation versus surgical CryoMaze alone for treatment of atrial fibrillation (SurHyb Trial): a protocol of the multicentre randomized controlled trial - Bulava, Alan; Mokracek, Ales; Wichterle, Dan; Budera, Petr; Osmancik, Pavel; Kacer, Petr; Veteskova, Linda; Nemec, Petr; Skala, Tomas; Santavy, Petr; Chovancik, Jan; Branny, Piotr; et al. (Journal of applied biomedicine, 2023)
BACKGROUND: Atrial fibrillation is common in patients with structural heart disease who are undergoing cardiac surgery. Surgical CryoMaze has been shown to be an effective treatment in several trials, but success rates have varied considerably, between 47-95%. The sequential hybrid approach, combining surgical CryoMaze followed by radiofrequency catheter ablation, can achieve high freedom from atrial arrhythmias. However, in patients with concomitant surgical atrial fibrillation treatment, data comparing the hybrid approach to CryoMaze alone are lacking. METHODS: The SurHyb study was designed as a prospective, open-label, multicentre randomized trial. Patients with non-paroxysmal atrial fibrillation who were scheduled for coronary artery bypass grafting or valve repair/replacement were randomized to either surgical CryoMaze alone or surgical CryoMaze followed by radiofrequency catheter ablation 3 months post-surgery. The primary outcome measure was arrhythmia-free survival without class I or III antiarrhythmic drugs, which has been evaluated using implantable cardiac monitors. CONCLUSIONS: This is the first randomized study that compares concomitant surgical CryoMaze alone with the staged hybrid surgical CryoMaze followed by catheter ablation, in patients with non-paroxysmal atrial fibrillation using rigorous rhythm monitoring. The results may contribute to the optimization of the treatment in patients undergoing concomitant CryoMaze for atrial fibrillation.
Keywords: Atrial fibrillation; Anti-Arrhythmia Agents; Cardiac Surgical Procedures; lidé; Catheter Ablation; výsledek terapie; Randomized Controlled Trials as Topic; prospektivní studie; katetrizační ablace; kardiochirurgické výkony; antiarytmika; Catheter ablation; Atrial Fibrillation; Humans; Prospective Studies; randomizované kontrolované studie jako téma; Cryomaze; multicentrické studie jako téma; Hybrid treatment; Treatment Outcome; fibrilace síní; Multicenter Studies as Topic